Maximum recoverable work and pseudofree energies for a rigid heat conductor - Amendola, G.; Bosello, C.A.; Fabrizio, M. (Інститут математики НАН України, 2007)
In this paper we consider the linear theory for a rigid heat conductor with memory effects for the heat flux in order to derive explicit formulae of the minimum free energy, which is related to the maximum recoverable work we can obtain by a given state of the body. Two equivalent forms of this work are given in the frequency domain. Finally, two different expressions of a thermodynamic potential, called pseudofree energy, are introduced for this material.